Synthesis of La0.7Sr0.3MnO3 at 800 degrees C using citrate gel method - Ravi, V.; Kulkarni, S. D.; Samuel, V.; Kale, Sangeeta N.; Mona, J.; Rajgopal, R.; Daundkar, A.; Lahoti, P. S.; Joshi, Rakesh S. (Ceramics International, 2007)
Manganite systems have been of considerable interest in the recent past due to their potential to operate in wide property range and also to serve as effective magnetic sensing and storing devices when synthesized using stringent conditions. We report a novel citrate gel method, in which La0.7Sr0.3MnO3 system has been synthesized at temperature 800 degrees C (LSMO800) with the synthesis duration is 6 h. The results have been compared with the sample synthesized at 1050 degrees C (LSMO1050). The synthesized bulk polycrystalline sample shows single-phase nature with the increase in particle size from similar to 50 nm to 300 nm with the increase in the sintering temperature. The magnetization data for LSMO800 shows well-defined hysteresis with saturation magnetization at around 1800 Oe and Curie temperature at 360 K, which is slightly lower than that of LSMO1050, which is 375 K. The results can be well attributed to the grain boundary effects. (C) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Citrate gel method; CMR; Oxides

La0.67Ce0.03Sr0.3MnO3-coupled microwave assisted ultra-fast synthesis of nanocrystalline cobalt oxide and Bismuth oxide - Rajagopal, Rajashree; Mona, J.; Joshi, Rakesh S.; Kale, Sangeeta N.; Pradhan, Sivararn; Gaikwad, A. B.; Ravi, V. (Materials Letters, 2008)
Bismuth hydroxide and Cobalt hydroxide gels were freshly prepared by adding aqueous sodium hydroxide to their corresponding nitrates under basic conditions. Then they were oven dried at 373 K and found to be amorphous in X-ray diffraction (XRD) study. They crystallized into their respective oxides by microwave irradiation (2.45 GHz) in merely 2 min using La0.67Ce0.03Sr0.3MnO3 (LCSMO) as couplant in a microwave domestic oven (similar to 100 W). This is the lowest temperature treatment and synthesis time so far reported in the literature for the formation of these systems. Formation of nanocrystallites of Bi2O3 (10 nm) and Co3O4 (15 nm) has been confirmed by XRD. Normally these hydroxides produce oxides only on heating at temperature >673 K or digesting them at 373 K for 4 - 6 hours as reported by us earlier. Microwave assisted heating proves to be a novel technology whose applications can be carefully harnessed due to its unique effects compared to the conventional heating, such as rapid volumetric heating, shortened reaction time and energy saving. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; Manganites; Microwave; Oxides

Microwave assisted low temperature rapid synthesis of manganite system using La0.67Ce0.03Sr0.3MnO3 mini-cavity furnace - Kale, Sangeeta N.; Rajagopal, Rajashree; Mona, J.; Londhe, D. P.; Joshi, Rakesh S.; Jagadale, Tushar C.; Satyanarayana, C.; Ravi, V. (Materials Letters, 2008)
Amorphous La0.7Sr0.3MnO3 (LSMO) and La0.7Ca0.3MnO3 (LCMO) precursor powders synthesized by the citrate gel method at 673 K, have been found to crystallize by microwave irradiation in just 60 s using La0.67Ce0.03Sr0.3MnO3 (Ce-LSMO) as couplant. This is the lowest temperature treatment and synthesis time so far reported in literature for the fort-nation of manganite systems. Using ceramic route, the same amorphous samples crystallize on heat treatment only at temperatures greater than 1000 K. The microwave heating through this method is novel and has tremendous potential for accelerating the evolution of the product phase in very shorter durations, with just low temperature processing of the precursors, which cannot be realized in normal process. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Citrate gel method; LSMO; Manganites; Microwave; Oxides

Carbon dioxide reforming of methane over ruthenium substituted strontium titanate perovskite catalysts - Gurav, Hanmant R.; Bobade, Richa; Das, Vineetha Lakshmi; Chilukuri, Satyanarayana V. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Strontium titanate (SrTiO3) doped with varying amounts of ruthenium (7.9, 15.6 and 31 wt%) have been prepared by the citrate gel synthesis method. Structural and textural characterizations reveal that at lower concentrations, a major part of Ru is incorporated in the lattice of SiTiO3. The content of surface Ru (outside lattice) increases with increasing amounts of the doped Ru. The surface Ru reduced at lower temperatures compared to Ru incorporated into the lattice. The reduction of the lattice substituted Ru occurs only at temperatures above the collapse of the perovskite structure. The catalyst sample with 7.9 wt% of Ru shows good conversions in the dry reforming of methane with CO2. The conversion of CO2 is in excess compared to methane under the studied reaction conditions. As a result, H-2/CO ratio of the product gases which should have been equivalent to unity is lower than the stoichiometric value. This ratio is particularly low when lower reaction temperatures (873-973 K) were used. Similar was the case when high space velocities were used. Low methane conversion and reverse water gas shift reaction are the causes for the low H-2/CO ratios.
Keywords: Carbon dioxide reforming; Catalysts; Citrate gel method; Doped catalysts; Dry reforming; Methane reforming; Perovskites; Reverse water gas shift; Ruthenium doped catalysts; Strontium titanate; Syngas

Effect of B site substitution in Gd2B2-xNiyO7-delta (B= Ti, Zr) ternary metal oxide catalysts in dry reforming of methane - Ghodke, Seema R.; Thundiyil, Shibin; Dongapure, Pavan; Devi, R. Nandini (Molecular Catalysis, 2022)
Structured catalysts are emerging as active and durable catalysts in dry reforming of methane due to their inherent characteristics like lattice insertion of active metals and consequent stability imparted. Here we report Ti and Zr substituted Gd2B2-xNiyO7-delta (B = Ti, Zr) catalysts synthesized by citrate gel method, which are characterized and tested for dry reforming of methane. Structure and Ni substitution has been confirmed by Rietveld refinement of powder XRD patterns and Raman analysis. TPR and CO2-TPD were performed to analyze the reducibility and effect of basic sites of catalysts in DRM activity. Ni doped Ti analogue shows stable and superior activity towards dry reforming of methane for 100 h. The in situ IR studies and XPS analysis confirmed the presence of surface hydroxyl species in this catalyst, which triggers the activation of CO2 and provides higher and durable activity in dry reforming reaction. Absence of any C formation in this catalyst after durability test indicates the mechanism of C gasification by the surface hydroxyl species enhancing stable activity for long durations.
Keywords: A(2)B(2)O(7); Citrate gel method; Dry reforming of methane; Ternary metal oxide